Trouble in Sport Paradise: Can Qatar Overcome the Diplomatic Crisis? - Dorsey,James M. (2018)
The crisis in the Gulf pitting a United Arab Emirates-Saudi-led alliance against Qatar is the least of the country's problems as it prepares for the 2022 FIFA World Cup. Indeed, Gulf States, primarily the United Arab Emirates (UAE), have long sought to discredit Qatar as a host prior to the UAE/Saudi Arabian declaration of a diplomatic and economic boycott in June 2017, yet Qatar has proven capable of addressing potential disruptions. However, the closer we come to the start of the tournament with the boycott still in place, the more difficult it will become for the boycotting states to include the World Cup in their embargo without provoking the ire of fans, attracting negative media coverage, and feeling pressured to concede.